2021
DOI: 10.1007/s10915-021-01704-8
|View full text |Cite
|
Sign up to set email alerts
|

On a Reconstruction of a Solely Time-Dependent Source in a Time-Fractional Diffusion Equation with Non-smooth Solutions

Abstract: An inverse source problem for a non-automonous time fractional diffusion equation of order (0 < β < 1) is considered in a bounded Lipschitz domain in R d . The missing solely time-dependent source is recovered from an additional integral measurement. The existence, uniqueness and regularity of a weak solution is studied. We design two numerical algorithms based on Rothe's method over uniform and graded grids, derive a priori estimates and prove convergence of iterates towards the exact solution. An essential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…This naturally contradicts the behavior of the solution near t = 0 as a lack of smoothness occurs due to the singular kernel of time Caputo fractional derivative. The authors in [13] extended the results to possibly nonsmooth solutions. They showed that Rothe's method on a uniform grid addresses the existence of a such a solution (non-smooth solutions are admissible with t γ term where 1 > γ > β with β the order of the fractional derivative) under low regularity assumptions, and that Rothe's method over graded grids has the advantage to cope better with the behaviour at t = 0 (also here t β is included in the class of admissible solutions) for the considered problems.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This naturally contradicts the behavior of the solution near t = 0 as a lack of smoothness occurs due to the singular kernel of time Caputo fractional derivative. The authors in [13] extended the results to possibly nonsmooth solutions. They showed that Rothe's method on a uniform grid addresses the existence of a such a solution (non-smooth solutions are admissible with t γ term where 1 > γ > β with β the order of the fractional derivative) under low regularity assumptions, and that Rothe's method over graded grids has the advantage to cope better with the behaviour at t = 0 (also here t β is included in the class of admissible solutions) for the considered problems.…”
Section: Introductionmentioning
confidence: 91%
“…These non-uniform meshes have the advantage to be flexible and reasonably convenient for practical implementation, however they can significantly complicate the analysis of the constructed Rothe schemes. As mentioned before, in [13], a similar problem is studied for M = 0 and f (x,t) = f (x). However, in this paper, we use the time-graded mesh properties side by side to obtain a crucial extension of Grönwall's inequalities for multiterm fractional operators, which is built on [14, Lemma 5.2] and an application of the classical discrete Grönwall inequality.…”
Section: Introductionmentioning
confidence: 99%
“…This type of measurement represents the weighted average of u over the domain Ω. And there are many literatures on inverse problems by this type measured data for fractional diffusion (wave) equations at present (see [9,32,39] and the references therein).…”
Section: (T)(u(t) ϕ) = (A(t)∇u(t) + B(t)u(t) ∇ϕ)mentioning
confidence: 99%
“…These mathematical problems have become a significant tool in simulating many real-life difficulties. For recent developments, one can see Hendy, and Bockstal in [33] for reconstruction of a solely time-dependent source in a time-fractional equation. Ansari et al in [34] study a class of distributed order fractional diffusion equation.…”
Section: Introductionmentioning
confidence: 99%